2020
DOI: 10.3390/rs12203293
|View full text |Cite
|
Sign up to set email alerts
|

UAS Imagery-Based Mapping of Coarse Wood Debris in a Natural Deciduous Forest in Central Germany (Hainich National Park)

Abstract: Dead wood such as coarse dead wood debris (CWD) is an important component in natural forests since it increases the diversity of plants, fungi, and animals. It serves as habitat, provides nutrients and is conducive to forest regeneration, ecosystem stabilization and soil protection. In commercially operated forests, dead wood is often unwanted as it can act as an originator of calamities. Accordingly, efficient CWD monitoring approaches are needed. However, due to the small size of CWD objects satellite data-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…A total of 4215 images, covering an area of 1.16 km 2 , were collected via parallel flights on five days during January 2019, resulting in a ground resolution of 1.63 cm per pixel. The images were processed with the software Agisoft Metashape Professional 1.5 (Agisoft, 2019a ) to reconstruct 3D-information from 2D-images (Kabiri et al, 2020 ; Kienholz et al, 2020 ; Thiel et al, 2020 ). This resulted in a digital surface model (DSM), a digital terrain model (DTM), and consequently in a normalized digital surface model (nDSM), showing the height of any object on the ground (for more detailed information see SI 1 and Fig.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 4215 images, covering an area of 1.16 km 2 , were collected via parallel flights on five days during January 2019, resulting in a ground resolution of 1.63 cm per pixel. The images were processed with the software Agisoft Metashape Professional 1.5 (Agisoft, 2019a ) to reconstruct 3D-information from 2D-images (Kabiri et al, 2020 ; Kienholz et al, 2020 ; Thiel et al, 2020 ). This resulted in a digital surface model (DSM), a digital terrain model (DTM), and consequently in a normalized digital surface model (nDSM), showing the height of any object on the ground (for more detailed information see SI 1 and Fig.…”
Section: Methodsmentioning
confidence: 99%
“…From an application standpoint, the two approaches conceptually most similar to ours use the Hough transform to fit lines representing individual stems in binarized images of target class posterior probabilities obtained on the basis of hand-crafted textural features (Duan et al, 2017) or spectral thresholding (Panagiotidis et al, 2019). Thiel et al (2020) performed generic line detection within RGB orthomosaics derived from very-high resolution unmanned aerial system-acquired imagery to find approximate fallen stem shapes.Lopes Queiroz et al ( 2019) used a generic segmentation procedure on the spectral bands of the aerial image combined with the normalized difference vegetation index (Tucker, 1979), and subsequently classified the resulting clusters based on spectral/textural features augmented with LiDAR derived information (canopy height model). Einzmann et al (2017) applied a similar approach, using large-scale mean shift in the role of the segmentation algorithm and augmenting the set of spectral bands with linear transformations of raw bands, textural features and multiple vegetation indices.…”
Section: Related Workmentioning
confidence: 99%
“…Santos et al (2019) made a comparison of three different deep learning frameworks, namely YOLOv3, Faster Region Based Convolutional Neural Networks (Faster R-CNN), and RetinaNet to assess a time series of RGB images in the context of tree crown detection achieving an overall average precision (AP) of 92%. Other studies have used object-based image analysis approach to detect coarse wood debris (CWD) from unmanned aerial systems in conjunction with LiDAR point clouds (Thiel et al, 2020). The authors reported an overall average precision (mAP) of 85% and a recall of 69.2%.…”
Section: Introductionmentioning
confidence: 99%